Audit Sistem Informasi Website Service Komputer Surabaya Menggunakan Framework COBIT 5 Domain DSS - Veby Pebiola Br Simanjorang; Nadilla Anidew; Muzayyanatul Wafiroh; Divane Infonya Safinatunnajah; Anita Wulansari (Pusat Riset dan Inovasi Nasional, 2024)
Service computer surabaya is one of the website-based gadget service businesses that still needs evaluation. Surabaya computer service website information system audit using the COBIT 5 framework with DSS domains and maturity level assessment. The research aims to evaluate the Surabaya computer service website information system. The results show that the average maturity level reached 3.93 (level 4 - Managed and Measurable) with an expected value at level 4. DSS04 has the highest value, while DSS01 has a significant gap. Recommendations include creating SOPs, problem identification, long-term monitoring, security improvements, and business process audits. In conclusion, the company needs to improve DSS01 and DSS03 while the other domains are good. It is hoped that this research can help in improving and maintaining services from service computer surabaya to provide the best service to users from managers.